Evaluation of Nigerian Government’s New Cashless Policy: Insights from Select National Dailies - Ndubuisi Nwakpa, James (British Journal of Marketing Studies, 2023)
The Central Bank of Nigeria (CBN) in a bid to reduce inflation and stabilize the country’s economy, introduced cashless policy in 2012. The move became more pronounced following the recent efforts to redesign the country’s 200, 500 and 1,000-naira local currency denominations, which resulted in high scarcity of money in circulation. Since then, the initiative has remained a contentious issue. This study appraised the level of success, impacts, challenges and prospects of the policy as reported in select Nigerian national daily newspapers. The study was anchored on the Diffusion of Innovation and Agenda Setting theories, while relying on secondary data, sourced from five Nigerian national daily newspapers. Manifest contents of the editorials/opinions and feature stories contained in the newspapers were analysed. Findings show that absence of appropriate legal/regulatory framework for e-payment; poor epileptic electric supply, illiteracy, lack of financial infrastructure; risk of identity theft and poor service from network providers were among the factors that hamper the success of the cashless policy in Nigeria. The paper holds that cashless society provides safer and more practical alternative means of transacting businesses than over reliance on physical cash, and that the initiative can improve on Nigeria’s economy only when well implemented, and calls on the government, financial institutions, network providers, academic institutions and other key stakeholders to work in synergy for a successful cashless economy to be achieved in Nigeria.